Research on atmospheric temperature change and its adaptive strategies in winter wheat and summer maize dual-cropping region of North China Plain during 1961-2021-A case study of Jiaozuo City in Henan Province. - Chengyuan Hao; Sunan He (PLoS ONE)
Global warming has caused the frequency and intensity of extreme weather events in agriculture. Therefore, research on temperature changes in major grain-producing areas is essential for formulating adaptation strategy. This article takes Jiaozuo City, Henan Province, China as the research area. Based on daily maximum, minimum and mean temperatures from seven meteorological stations for the period 1961-2021, the comprehensive indications of temperature changes were analyzed using the linear tendency estimation, Mann-Kendall test, and levels fluctuation. Fourteen climate indices in four classes, including the mean temperature index, absolute extreme temperature index, relative extreme temperature index, and disaster temperature index, were applied. The results indicated four aspects. Firstly, the average regional warming speed was 0.259°C/10a-slightly lower than the national average, and the years of the highest and lowest values were 2021 and 1984, respectively. Secondly, the daily minimum and maximum temperatures increased significantly, which were 0.395°C/10a and 0.200°C/10a respectively-less than the national mean. The relevant low temperature index showed proper decreasing trend while the diurnal range of annual extreme temperature showed fluctuating-decreasing first and then increasing. Thirdly, the relevant e high temperature indices of plain urban area were larger while the relevant low temperature indices of mountain hilly area were smaller. The relative high temperature indices showed an increasing trend while the relevant low temperature indices tended to decrease. Fourthly, high temperature disasters generally declined before the 1980s and increased thereafter; low temperature disasters showed a decreasing trend overall. This study suggests that in the two-cropping regions of winter wheat and summer maize, attention should be paid to the increasing trend of high-temperature days. Additionally, heat-tolerant varieties should be cultivated to expand the planting area of maize for adapting to increasing drought disasters induced by high temperature, as well as to establish an agricultural disaster-risk mechanism for addressing high temperature meteorological disasters.